Faith in war. Religion and the military in Germany, 1500–1650. - Nelson, Samantha (Journal of Ecclesiastical History, 2026)
The article focuses on Nikolas Funke’s book *Faith in War*, which reevaluates the religious beliefs and behaviors of early modern soldiers within the Holy Roman Empire, challenging stereotypes of soldiers as irreligious or solely motivated by confessional conflict. Funke argues that military authorities promoted confessional coexistence and that soldiers often expressed religiosity through shared Christian values rather than strict denominational identities, while also engaging in behaviors considered deviant by religious norms. Utilizing sources such as legal codes and autobiographical accounts, the book highlights soldiers’ ability to separate religious convictions from military roles, suggesting a more nuanced understanding of confessional conflict during this period. Although the study primarily focuses on the Holy Roman Empire and lacks extensive comparative analysis with other European armies, it offers significant insights into the interplay between religion, military culture, and social norms in early modern warfare.